Mangrove Ecosystem Management Strategy in Maron Beach Semarang - Alin Fithor; Joko Sutrisno; Agus Indarjo (Marine Science Department Diponegoro University, 2018)
Management of mangrove ecosystem is an important agenda in conserving tourism spots in coastal area. This research aimed at examining the recreation activities done in mangrove ecosystem area and mangrove forest strategy in Maron Beach, Tambakharjo, Semarang Municipality. This research employed a survey approach using direct interviews and field observations. The repondent included the entire population in the research area. Samples of this study were selected using cluster random sampling technique. Data were collected by observations, interviews and document study, followed by SWOT analysis. The results showed that the opening of Maron Beach recreation area has given some negative impacts to the post-rehabilitation of mangrove ecosystems, reducing the function mangrove in protecting the shore from coastal abrasion, reducing ability of wind abrasion protection, weakening the environmental conditions, decreasing the number of visitors and decreasing the production of fish. Mangrove forest management should be progressive, which means that research should be done in poor and unsteady conditions which result allow the market to continuously expand, enlarge the market growth and maximize the progress. Through the implementation of a non-overlapping effort, this condition can be improved.